Evaluation de la qualité de l’ananas (Ananas comosus (L.) Merr.) de cinq itinéraires techniques de production dans la Commune d’Allada au Bénin. - AZONKPIN, Saturnin; CHOUGOUROU, CHÈPO DANIEL; ABOUDOU, K.; HEDIBLE, Luc; SOUMANOU, MANSOUROU MOHAMED (My University, 2019)
Pineapple grown under optimal conditions, allows to obtain fruits of good quality which can generate important currencies to the exportation. In order to contribute to the improvement of pineapples quality produced in Benin, an assessment of the quality of fruit and pineapple juice from the five most productive technical itineraries (It13, It14, It75, It77, It78) selected from an earlier study, was performed through sensory and physico-chemical analyzes in the laboratory. Thus, the size, color, shape of the crown, the presence of sunburn, insect hole, deformation, cracking and mealybugs were evaluated on the fruit. The dry matter content of juice and pulp, density, pH, titratable acidity, soluble dry matter and total sugar content were evaluated on fruit and juice. An analysis of the variance made it possible to discriminate the technical itineraries according to these parameters. It is noted that the fruits have a good color, a good caliber and a good crown. They are without sunburn, insect holes, deformities, cracks and scale insects. Juice density ranged from 1.02 to 1.05. The dry matter contents of juices and pulp ranged from 11.40% to 15.94% and from 14.04% to 18.07%, respectively. The pH of the juices is ranged from 3.76 to 4.62, while the soluble dry matter of the juices is ranged from 12.70 to 17.37 ° Brix. The total sugar content of the juices is ranged from 12.99 to 29.97 mg / 100 g. The sugar loaf variety '' Abacaxi '' has a low acidity and a higher pH. Overall, all the fruits from these technical itineraries presented sensory and physicochemical qualities that are conform to the requirements of the Quality and Packaging Promotion Department in 2005, then that of the UNECE FFV standard. 49 of November 2012. The It75 technical route got the best physicochemical quality of fruit and pineapple juice, while the best sensory quality of fruit was obtained at It77.
Keywords: Sensory quality; physico-chemical quality; Ananas comosus; fruit; juice.